Low-permeability Fiber-reinforcement Concrete of Composite Binder - Fediuk, R; Mochalov, A; Timokhin, R (IOP conference series. Materials Science and Engineering, 2018)
The subject of this work is the low permeable concrete which is produced by a novel composite binder. The binder is produced through joint grinding of the Portland cement, fly ash, and limestone together with superplasticizer using a vario-planetary mill. Grinding of active mineral supplements allows crystallization of ash particles as a result of the binding of Ca(OH)2 during hardening alite, which intensifies the clinker minerals hydration process; the presence of fine grains limestone also leads to the hydrocarboaluminates calcium formation. The highest strength has been measured when 45 wt.% of Portland cement is replaced with industrial waste. This higher strength of milled Portland cement is due to the increased formation of "needle-like" and "stem-like" crystals. In general, the reduction in capillary porosity of compositions modified by the technogenic waste more than 2 times should be noted for all specimens compared with reference specimen.